Causes and Timing of Mortality and Morbidity Among Late Presenters Starting Antiretroviral Therapy in the REALITY Trial. (4th March 2018) - Post, Frank A; Szubert, Alexander J; Prendergast, Andrew J; Johnston, Victoria; Lyall, Hermione; Fitzgerald, Felicity; Musiime, Victor; Musoro, Godfrey; Chepkorir, Priscilla; Agutu, Clara; Mallewa, Jane; Rajapakse, Chathurika; et al.
Abstract: Background: In sub-Saharan Africa, 20%–25% of people starting antiretroviral therapy (ART) have severe immunosuppression; approximately 10% die within 3 months. In the Reduction of EArly mortaLITY (REALITY) randomized trial, a broad enhanced anti-infection prophylaxis bundle reduced mortality vs cotrimoxazole. We investigate the contribution and timing of different causes of mortality/morbidity. Methods: Participants started ART with a CD4 count <100 cells/µL; enhanced prophylaxis comprised cotrimoxazole plus 12 weeks of isoniazid + fluconazole, single-dose albendazole, and 5 days of azithromycin. A blinded committee adjudicated events and causes of death as (non–mutually exclusively) tuberculosis, cryptococcosis, severe bacterial infection (SBI), other potentially azithromycin-responsive infections, other events, and unknown. Results: Median pre-ART CD4 count was 37 cells/µL. Among 1805 participants, 225 (12.7%) died by week 48. Fatal/nonfatal events occurred early (median 4 weeks); rates then declined exponentially. One hundred fifty-four deaths had single and 71 had multiple causes, including tuberculosis in 4.5% participants, cryptococcosis in 1.1%, SBI in 1.9%, other potentially azithromycin-responsive infections in 1.3%, other events in 3.6%, and unknown in 5.0%. Enhanced prophylaxis reduced deaths from cryptococcosis and unknown causes ( P < .05) but not tuberculosis, SBI, potentially azithromycin-responsive infections, or other causes ( P > .3); and reduced nonfatal/fatal tuberculosis and cryptococcosis ( P < .05), but not SBI, other potentially azithromycin-responsive infections, or other events ( P > .2). Conclusions: Enhanced prophylaxis reduced mortality from cryptococcosis and unknown causes and nonfatal tuberculosis and cryptococcosis. High early incidence of fatal/nonfatal events highlights the need for starting enhanced-prophylaxis with ART in advanced disease. Clinical Trials Registration: ISRCTN43622374.